2018
DOI: 10.3389/fpubh.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent emm Types among Invasive GAS in Europe and North America since Year 2000

Abstract: BackgroundStreptococcus pyogenes or group A streptococcus (GAS) is an important human pathogen responsible for a broad range of infections, from uncomplicated to more severe and invasive diseases with high mortality and morbidity. Epidemiological surveillance has been crucial to detect changes in the geographical and temporal variation of the disease pattern; for this purpose the M protein gene (emm) gene typing is the most widely used genotyping method, with more than 200 emm types recognized. Molecular epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
63
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 83 publications
(115 reference statements)
10
63
0
3
Order By: Relevance
“…emm1 is the most popular type in Germany, consistent with that in the USA, Australia, and Japan; the prevalent types were emm1 (31.8%), emm28 (15.4%), and emm 89 (14.5%) [14,32]. Presently, the most popular emm types in China are emm12 and emm1.…”
Section: Discussionsupporting
confidence: 59%
“…emm1 is the most popular type in Germany, consistent with that in the USA, Australia, and Japan; the prevalent types were emm1 (31.8%), emm28 (15.4%), and emm 89 (14.5%) [14,32]. Presently, the most popular emm types in China are emm12 and emm1.…”
Section: Discussionsupporting
confidence: 59%
“…[22,23] The diagnosis of GAS meningitis in our case is further strengthened by the mother's positive throat swab which revealed the same GAS subtype as that of the neonate's CSF culture. Several recently published epidemiological studies [24][25][26] have revealed that the emm1.0 subtype identified in our case is the most prevalent subtype causing invasive GAS infections, and specifically meningitis, in the majority of European and North American countries. Moreover, emm1.0 is associated with death from invasive GAS infections at all ages.…”
Section: Discussionsupporting
confidence: 52%
“…For the last two decades, a significant increase in the number of invasive infections has been seen in certain regions of North America and Europe. Gheradi et al [95] have shown several serotypes have increased their circulation in these areas. While between 50 and 70% have been associated with one particular serotype, emm1, the risk of complications associated with the other serotypes, including known invasive members such as emm3, emm12 and emm28 [96] as well as emm59 [97] and emm89 [98].…”
Section: Invasive Streptococcus Pyogenesmentioning
confidence: 98%